2017
DOI: 10.1128/jmbe.v18i1.1253
|View full text |Cite
|
Sign up to set email alerts
|

Student Misconceptions about Plants – A First Step in Building a Teaching Resource

Abstract: Plants are ubiquitous and found in virtually every ecosystem on Earth, but their biology is often poorly understood, and inaccurate ideas about how plants grow and function abound. Many articles have been published documenting student misconceptions about photosynthesis and respiration, but there are substantially fewer on such topics as plant cell structure and growth; plant genetics, evolution, and classification; plant physiology (beyond energy relations); and plant ecology. The available studies of misconc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 19 publications
0
17
0
2
Order By: Relevance
“…In a study with science teachers, Kwen (2005) observed multiple teachers holding misconceptions like each plant type is limited to one reproductive method whereas some plants are adept with several methods to reproduce. The belief that 'plants absorb food from the soil' was appeared to be utterly common in postgraduates and teacher trainees (Wynn et al, 2017). 38% of preservice science teachers participating in a study by Crawley and Arditzoglou (1988) reflected misconceptions in three out of four topics in plant biology.…”
Section: Discussionmentioning
confidence: 99%
“…In a study with science teachers, Kwen (2005) observed multiple teachers holding misconceptions like each plant type is limited to one reproductive method whereas some plants are adept with several methods to reproduce. The belief that 'plants absorb food from the soil' was appeared to be utterly common in postgraduates and teacher trainees (Wynn et al, 2017). 38% of preservice science teachers participating in a study by Crawley and Arditzoglou (1988) reflected misconceptions in three out of four topics in plant biology.…”
Section: Discussionmentioning
confidence: 99%
“…Συγχρόνως, ένας σημαντικός αριθμός ερευνητών εστιάζει σε μία από τις πτυχές του φαινομένου, που σχετίζεται με το πλήθος των παρανοήσεων που αναπτύσσουν οι μαθητές για τους φυτικούς οργανισμούς. Οι παρανοήσεις αυτές φαίνεται να διατρέχουν διάφορα αντικείμενα της επιστήμης των φυτών, όπως η κυτταρική δομή, η φυσιολογία, το αναπαραγωγικό σύστημα και η γενετική (Wynn et al, 2017) και εκτείνονται ακόμη και στην αδυναμία των μαθητών να χαρακτηρίσουν τα φυτά ως ζωντανούς οργανισμούς (Amprazis et al, 2021). Ειδικότερα, η αναπαραγωγική λειτουργία αποτυπώνεται ως ένα εν γένει δυσνόητο αντικείμενο διδασκαλίας, ιδιαιτέρως όταν απαιτείται να συνδυαστεί με τα αναπτυξιακά στάδια του φυτού (Etobro & Fabinou, 2017· Lampert et al, 2019, 2020· Maskour et al, 2019.…”
Section: Eισαγωγήunclassified
“…Beste aldetik, landareen fisiologiari buruzko ezagutza Bigarren Hezkuntzan zehar progresio nabariena jasan zuen aldagaia izan arren (H = 32,945, p < 0,001), bibliografian sakonki dokumentatutako kontzepzio alternatiboak azaleratu ziren ikasleen erantzunetan (Wynn et al, 2017). Adibidez, ikasleen %89-ak oker adierazi zuen landareek biomasa lurretik lortzen dutela, eta arnasketa eta fotosintesiarekin erlazionatutako kontzepzio alternatiboak ohikoak izan ziren ere (e.g.…”
Section: Ikerketaren Muina Eta Ondorioakunclassified